Measurement of radon in ground waters of the Western Caucasus for seismological application. (November 2015) - Nevinsky, I.; Tsvetkova, T.; Nevinskaya, E.
Abstract: Results of radon ( 222 Rn) concentration measurement in ground waters in the Western Caucasus are described. In 2010–2011 each day at 12:00 Moscow winter time (9:00 GMT) sampling in volume of 0.5 l of waters was carried out in two wells at depth of 30 m and 180 m. In 2012 three times per day (7:00, 12:00, 17:00) this sampling was already carried out. Radon from water was extracting by degassing method with use of bubbler. Measurements of alpha activity of gas in scintillation (ZnS) chambers were done. The water radon data with seismic, meteorological and the Sun-Lunar data were compared. The mathematical method of definition of "splashes" in radon data before regional earthquakes is considered. The greatest probability in 72% of the forecast of regional earthquakes for the data from a well of 30 m depth was received. Correlation between meteo and radon data is absent. Correlation of lunar phases and solar activity with radon data is discussed. In July–December, 2012 sampling of water from 15 wells and measurements of radon were carried out. The distance between wells was near 50 km. Changes of radon maps in territory of South Russia during earthquakes are shown. Highlights: Changes of radon concentration in ground waters before earthquakes are shown. The identical periods of variations radon and the Sun-Lunar data are described. Meteorological data do not correlate with radon data.